REGULATION OF THE USE OF CRYPTOCURRENCY: TECHNOLOGIES, LIMITATIONS, AND DEVELOPMENT PROSPECTS - Afanasievna Lapina, Marina; Alexandrovna Pogrebinskaya, Ekaterina; Nazarov, Vladimir; Katys , Petr (Revista Inclusiones, 2020)
The article is devoted to studying the current state of legal regulation of cryptocurrency circulation. Cryptocurrency has appeared relatively recently and immediately gained popularity among a certain part of users of modern financial services, as well as a misunderstanding or even complete rejection by others. In different states, the attitude to cryptocurrency also varies. Some countries, while allowing for the circulation of cryptocurrency, are developing its legal regulation, others have failed to find a better solution than to impose restrictions or even a complete ban.